2005
DOI: 10.1111/j.1365-2672.2005.02672.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state fermentation of cornmeal with the basidiomycete Ganoderma lucidum for degrading starch and upgrading nutritional value

Abstract: Aims: The objective of this research was to study the ability of the basidiomycete Ganoderma lucidum to degrade starch and upgrade nutritional value of cornmeal during solid-state fermentation (SSF). Methods and Results: On the basal medium that consisted of cornmeal and salt solution, a-amylase activity of G. lucidum reached its maximum value of 267 U g)1 of culture on day 20 after inoculation. Prolongation of fermentation time from 10 to 25 days increased significantly the degradation rate of starch and ergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Similarly, Han et al (2005) reported that Basidiomycete Ganoderma lucidum gave the highest starch degradation with yeast extract. This is in agreement with the observation of Cherry et al (2004) who reported that the fungus A. fumigatus produces high amylase activity with yeast extract.…”
Section: Effect Of Nitrogen Sources On Glucoamylase Productionmentioning
confidence: 86%
“…Similarly, Han et al (2005) reported that Basidiomycete Ganoderma lucidum gave the highest starch degradation with yeast extract. This is in agreement with the observation of Cherry et al (2004) who reported that the fungus A. fumigatus produces high amylase activity with yeast extract.…”
Section: Effect Of Nitrogen Sources On Glucoamylase Productionmentioning
confidence: 86%
“…For instance, in a recent study, ergosterol of basidiomycete Ganoderma lucidum was used to study its growth after its solid state fermentation on cornmeal (Han et al 2005). In our study, all isolates exhibited different growth response on different SSF substrates as evidenced by varying amount of ergosterol produced (Table 2).…”
Section: Ergosterol Based Biomass Estimationmentioning
confidence: 88%
“…Amylases are widely distributed enzymes in plants, animals, and microorganisms, but bacterial enzymes are in the greatest demand at the industrial level (Pandey et al 2000;Gupta et al 2003), even though there are reports that indicate that certain fungi are good amylase producers (Das and SenMandi, 1992;Pal et al 1980). There are studies where amylases of basidiomycetes have been exploited in order to increase the nutritional value of agroindustrial residues in the livestock industry (Han 2003;Han et al 2005). Thus, knowing the amylolytic potential of the isolates makes it possible to obtain new producers of amylases that can be used for the development of digestive adjuvants.…”
Section: Plate Screening For Degrading Enzymes Of Plant Cell Wall Commentioning
confidence: 99%